Homocysteine and the Mortality of Critically Ill Patients: A Meta-Analysis - Yuan, Fawei; Zheng, Kun (Hormone and Metabolic Research, 2022)
Prevalence of hyperhomocysteinemia (HHcy) is high in critically ill patients. However, the association between serum homocysteine level and outcomes of the critically ill patients remains unknown. We performed a meta-analysis of cohort studies to comprehensively evaluate the above association. Relevant cohort studies were identified by search of electronic databases including PubMed, Embase, Web of Science, Wanfang, and CNKI from the inception of the databases to February 5, 2022. A randomized-effect model incorporating the possible between-study heterogeneity was used to pool the results. Overall, 16 cohorts with 1663 critically ill patients who were admitted to the intensive care unit (ICU) were involved in the meta-analysis. Pooled results showed that compared to non-survivors of the critical illnesses, survivors had significantly lower serum level of Hcy at ICU admission [mean difference (MD): –3.42 μmol/l, 95% confidence interval (CI): –5.89 to 0.94, p=0.007; I2=86%]. Subgroup analysis showed that the difference of Hcy between survivors and non-survivors was significant in Asian patients (MD: –8.17 μmol/l, p<0.001), but not in non-Asians (MD: 0.30 μmol/l, p=0.62; p for subgroup difference<0.001). Moreover, meta-analysis with seven cohorts, all including Chinese patients, showed that HHcy at ICU admission was independently associated with a higher risk of all-cause mortality in critically ill patients (odds ratio: 2.99, 95% CI: 2.26 to 3.97, p<0.001; I2=69%). A higher serum level of Hcy at ICU admission may be associated with an increased risk of all-cause mortality in critically ill patients, particularly in the Chinese population.
Keywords: homocysteine; hyperhomocysteinemia; critically ill; mortality; meta-analysis